Environment-Friendly Approach to Isolate Ascorbic Acid from Plants and Micro-identified Using Fourier Transform Infrared Spectroscopy - Muhammad Abdurrahman, Munir; Jamia Azdina, Jamal; Ahlam, Inayatullah (American Chemical Society, 2024)
Vitamin C [ascorbic acid (AA)] is an imperative antioxidant that humans require. Fruits and vegetables commonly contain AA. The application of titrimetric or chromatographic methods is generally performed to analyze AA; nevertheless, these approaches have several disadvantages such as being very costly for chromatographic methods and exhibiting food color interference upon using titration techniques. This study cruises the application of microwave treatment on AA compounds of plant samples and identified the AA level using Fourier transform infrared (FTIR) spectroscopy. The purposes of this study were to establish a validated method for the microwave-assisted isolation (MAI) of AA from plant samples. Validation studies such as linearity, selectivity, sensitivity, detection, and quantitation limits were evaluated using a standard AA solution. These methods were also applied for AA quantitation in oranges, guava, and spinach. The methods were selective and sensitive when applied to the standard solution. The FTIR spectroscopy approach was more sensitive, with lower values for detection limit (13.76 nmol·L−1 ) and quantitation limit (41.69 nmol·L−1 ), and more accurate with an error of less than 1%. The imperative AA groups are also identified, such as the hydroxyl groups found at 3297 nm−1 . In contrast, the aromatic group of AA can be obtained at 2084 cm−1 , although the absorption intensity is weak. The 1635 cm−1 atom is related to the carbonyl group (−CO). The validated method was applied to investigate the AA level in plant samples, and all of them showed identical peaks with the standard, showing that the MAI has isolated the AA completely.